2018
DOI: 10.4314/ovj.v8i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical response to a lomustine/cytarabine-based chemotherapy protocol in a case of canine large granular lymphocyte T-cell lymphoma with spinal involvement

Abstract: A 7-year-old, female neutered cross-breed dog was referred to our institution with a history of progressive hind limb weakness, which then progressed to paraplegia. An MRI of the spine revealed severe meningeal infiltrate consistent with lymphoma involvement, located at the level of L2-L7 with concurrent lymph node enlargement and abnormal bone marrow. Abdominal ultrasonography also identified changes in the spleen and confirmed enlargement of the lumbar aortic lymph node. Cytology of lymph nodes and spleen co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 13 publications
3
14
1
Order By: Relevance
“…In canine LGL lymphoma of the skin and intestine treated with chemotherapy with CHOP and surgery (the intestinal lymphoma in this report was localized and may have been completely removed by surgery), relatively long survival times of 508 days have also been reported [5]. Especially, dogs with spinal or cutaneous/intestinal LGL lymphoma were positive for clonal rearrangement of T-cell receptor in PARR analysis, as observed in the present case, and each of them experienced relatively long survival [5,16]. In contrast, other cases of T-cell LGL lymphomas, anatomically classified as splenic, hepatosplenic, or ocular, had short survival durations (6-68 days); all of these cases showed lymphoma-associated hemophagocytic syndrome [13], which was not detected in the present case.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…In canine LGL lymphoma of the skin and intestine treated with chemotherapy with CHOP and surgery (the intestinal lymphoma in this report was localized and may have been completely removed by surgery), relatively long survival times of 508 days have also been reported [5]. Especially, dogs with spinal or cutaneous/intestinal LGL lymphoma were positive for clonal rearrangement of T-cell receptor in PARR analysis, as observed in the present case, and each of them experienced relatively long survival [5,16]. In contrast, other cases of T-cell LGL lymphomas, anatomically classified as splenic, hepatosplenic, or ocular, had short survival durations (6-68 days); all of these cases showed lymphoma-associated hemophagocytic syndrome [13], which was not detected in the present case.…”
supporting
confidence: 56%
“…The response rate in cats treated with combination chemotherapy with COP (vincristine, prednisolone, and cyclophosphamide) and CHOP (COP plus doxorubicin) was 30% (5%, complete remission; 25%, partial remission) [7]. In canine spinal, mediastinal, splenic and hepatosplenic LGL lymphoma, several chemotherapy protocols combining lomustine, vincristine, procarbazine, and prednisolone, lomustine and cytarabine, or lomustine and cyclosporine A have been reported [10,13,16]. In a dog with LGL lymphoma of the skin and intestine, combination chemotherapy with CHOP has been performed [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Review of previously reported cases reveals a mean age of 9 years (range 4-14) across 41 cases. 5,14,[16][17][18][19][20][21][22][23] Across these previous publications, a male to female ratio of 0.7:1 was identified in contrast to the current study where male dominance was identified.…”
Section: Discussioncontrasting
confidence: 71%
“…Across the previous canine case reports, anaemia was identified in 56% of cases, neutrophilia in 49% of cases, thrombocytopaenia in 25% of cases and neutropenia in 17% of cases (some cases exhibited more than one cytopaenia). 5,14,[16][17][18][19][20][21][22][23] In comparison with the current study, these previously reported cases exhibited anaemia at nearly three times the occurrence and thrombocytopaenia at nearly two times the occurrence, while the incidence of neutrophilia was similar.…”
Section: Discussionsupporting
confidence: 54%